[About CEU - Part 8]
Promotional video about the CEU Conference and Residence Center situated on Kerepesi street in Budapest, Hungary. Footage of the exterior, the interior (rooms, computer labs, conference halls), the details of the building as well as the surroundings. The recording contains several interviews with students living in the dormitory.